2020
DOI: 10.3389/fendo.2019.00883
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risks and Benefits of Medications Used for Weight Loss

Abstract: Obesity is a complex disease influenced by many neurohormonal pathways which regulate body weight toward homeostasis. Presently, the disease of obesity effects over a billion individuals worldwide with scalable treatment options in dire need. Pharmacologic interventions for obesity have been developed to help promote weight loss in individuals with obesity. This area is rapidly developing and will only exponentially increase to serve the demand for persons with obesity seeking biologically orientated solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…As with other diseases such as diabetes and hypertension, PCPs must understand the key biological underpinning of obesity and use any tools available for treatment, including pharmacotherapy. Additionally, some anti-obesity medications, such as glucagon-like peptide 1-receptor agonists (GLP-1RAs), have beneficial effects on cardiovascular outcomes and mortality [ 42 , 43 ].…”
Section: A Review On Current Treatments For Obesitymentioning
confidence: 99%
“…As with other diseases such as diabetes and hypertension, PCPs must understand the key biological underpinning of obesity and use any tools available for treatment, including pharmacotherapy. Additionally, some anti-obesity medications, such as glucagon-like peptide 1-receptor agonists (GLP-1RAs), have beneficial effects on cardiovascular outcomes and mortality [ 42 , 43 ].…”
Section: A Review On Current Treatments For Obesitymentioning
confidence: 99%
“…RK pretreatment reduced isoproterenol-induced cardiac tissue damage and dyslipidemia [ 19 , 20 ]. Because obesity therapeutic agents often are associated with adverse cardiovascular events [ 21 ], the RK doses that prevent weight gain should also be examined for their hemodynamic effects. Indeed, weight loss nutraceuticals are typically consumed on a long-term basis for several months, therefore, understanding the cardiovascular risks and benefits are critical for their assessment.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies looking at long-term effects of these medications on weight loss have found improvements in blood pressure (BP), biomarkers for cardiovascular disease, and T2DM-related comorbidities. 3,5,7 Positive effects on comorbidities have been found to be related to drug class and mechanism of action (MOA); those that also are approved for T2DM have demonstrated the most favorable cardiovascular effects. 7 Other medications that work as stimulants or as modulators of serotonin pathways are associated with increased risks, prompting the US Food and Drug Administration (FDA) to remove some medications from the market.…”
mentioning
confidence: 99%
“…3,5,7 Positive effects on comorbidities have been found to be related to drug class and mechanism of action (MOA); those that also are approved for T2DM have demonstrated the most favorable cardiovascular effects. 7 Other medications that work as stimulants or as modulators of serotonin pathways are associated with increased risks, prompting the US Food and Drug Administration (FDA) to remove some medications from the market. 7,8 In January 2020, lorcaserin was taken off the market because of increased risk of cancer found in postmarketing surveillance.…”
mentioning
confidence: 99%
See 1 more Smart Citation